2017
DOI: 10.1159/000471808
|View full text |Cite
|
Sign up to set email alerts
|

Thiadiazolidinone-8 Ameliorates Inflammation Associated with Experimental Colitis in Mice

Abstract: Thiadiazolidinone-8 (TDZD-8) is an effective thiadiazolidinone derivate that is able to suppress the expression of inflammatory cytokines; it also presents tissue protective actions by glycogen synthase kinase (GSK)-3β inhibition, promoting thus an anti-inflammatory effect. Since inflammatory bowel disease is a chronic disease with reduced quality of life, where currently available therapies are only able to induce or maintain the patient in remission, it is crucial to investigate new pharmacological approache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 33 publications
6
14
0
Order By: Relevance
“…This data is consistent with other previous findings, where anti-inflammatory drugs are able to decrease ALP level. 17 , 31 , 34 Furthermore, as intestinal ALP is expressed on the enterocytes and it is responsible for the mucosal defense, 35 , 36 our findings also suggest that hemin had a cytoprotective effect on the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 53%
See 3 more Smart Citations
“…This data is consistent with other previous findings, where anti-inflammatory drugs are able to decrease ALP level. 17 , 31 , 34 Furthermore, as intestinal ALP is expressed on the enterocytes and it is responsible for the mucosal defense, 35 , 36 our findings also suggest that hemin had a cytoprotective effect on the intestinal mucosa.…”
Section: Discussionsupporting
confidence: 53%
“…In our study, the intensity of hemorrhagic focus was evaluated by the fecal hemoglobin concentration. 17 , 31 We observed that hemin treatment produced a considerable influence in the intensity of hemorrhagic focus, because the fecal hemoglobin concentration significantly decreased in a dose-dependent manner after a daily dose of hemin. This finding suggests that hemin-treated mice presented an amelioration of the active inflammatory disease identified in mice with TNBS-induced colitis.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Taken together, these findings support EPO's potential to activate anti-apoptotic signaling in dopaminergic neurons in vivo, which if true, would support an anti-apoptotic role of EPO in the nigrostriatal system and a possible mechanism of its protective activity. One possibility in this regard is that EPO may be exerting anti-apoptotic effects through the Bcl-2 family proteins via multiple Luo et al, 2016;Mateus et al, 2017;Nakamura et al, 2015;Villa et al, 2003). Reductions in TNF-α and IL-6, along with reduced astrocyte activation and microglial recruitment have also been reported in a rat model of ischemia (Villa et al, 2003).…”
Section: Epo In Animal Models Of Diseasementioning
confidence: 99%